Politics and problematics of the definition and categorization of ethnicity in Nepal - Pokharel, Ramesh (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 1-15 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8042